Ground-Based GNSS and Satellite Observations of Auroral Ionospheric Irregularities during Geomagnetic Disturbances in August 2018 - Irina Zakharenkova; Iurii Cherniak; Andrzej Krankowski (Sensors, 2021)
The 25–26 August 2018 space weather event occurred during the solar minimum period and surprisingly became the third largest geomagnetic storm of the entire 24th solar cycle. We analyzed the ionospheric response at high latitudes of both hemispheres using multi-site ground-based GNSS observations and measurements onboard Swarm and DMSP satellites. With the storm development, the zones of intense ionospheric irregularities of auroral origin largely expanded in size and moved equatorward towards midlatitudes as far as ~55–60° magnetic latitude (MLAT) in the American, European, and Australian longitudinal sectors. The main ionospheric trough, associated with the equatorward side of the auroral oval, shifted as far equatorward as 45–50° MLAT at both hemispheres. The interhemispheric comparison revealed a high degree of similarity in a large expansion of the auroral irregularities oval towards midlatitudes, in addition to asymmetrical differences in terms of larger intensity of plasma density gradients and structures over the Southern auroral and polar cap regions. Evolution of the intense ionospheric irregularities and equatorward expansion of the auroral irregularities oval were well correlated with increases of geomagnetic activity and peaks of the auroral electrojet index.